2010
DOI: 10.1177/0020872810368394
|View full text |Cite
|
Sign up to set email alerts
|

Social work practitioners and subjective well-being: Personal factors that contribute to high levels of subjective well-being

Abstract: Based on interviews with social workers possessing the highest level of subjective well-being (SWB) from a 2006 Canadian survey, this research identifies personal factors, including personal behaviors, interpersonal relationships and manifestations of self beyond their workplace and identity as social workers, as positively influencing social work practitioners' high levels of subjective well-being. The conclusion considers implications for social work practice, education, and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 24 publications
0
27
0
4
Order By: Relevance
“…Although it is also likely that people who scored high on the measures of work and profession satisfaction would have insights about those things that contribute to their high levels of satisfaction, previous research has shown that those insights tend to be more general (see e.g. Graham & Shier, 2010a, 2010bShier & Graham, 2011), therefore impacting…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is also likely that people who scored high on the measures of work and profession satisfaction would have insights about those things that contribute to their high levels of satisfaction, previous research has shown that those insights tend to be more general (see e.g. Graham & Shier, 2010a, 2010bShier & Graham, 2011), therefore impacting…”
Section: Methodsmentioning
confidence: 99%
“…intrapersonal dynamics) along with individual perspectives about overall life and job satisfaction (Diener, 1984;. By building knowledge about those factors and conditions that social workers are evaluating, and which contribute to their overall perceived well-being, we can help identify strengths, which then can be leveraged towards improving occupational conditions in the field (Graham & Shier, 2010a,2010b, and in the case of the negative impact of perceived expectations on social worker well-being, a basis can be provided for social worker training and education.…”
Section: Introductionmentioning
confidence: 99%
“…Openness to emotional expression and the capacity to create a playful group identity are connected to well-being in temporary groups (Terrion & Ashforth, 2002), while the ability to have open relationships and express one's personal characteristics is seen as a factor in subjective well-being and at the same time as a factor capable of increasing the productivity of those who work in social service organizations (Graham & Shier, 2010, 2011). …”
Section: Relational Interactionmentioning
confidence: 99%
“…Ello pudiera tener por un lado, relación con el hecho de que fueron entrevistados profesionales de diferentes disciplinas tal como lo reportó el estudio de trabajadores de salud alemanes. En ese estudio hubo diferencias en la conceptualización del constructo entre médicos y enfermeras (12). Es decir, que entre los profesionales de la salud podría haber diferenciales culturales propias de la formación académica recibida, y al no pertenecer todos los participantes a la misma (como ya se indicó se incluyeron médicos, enfermeras y otras profesiones) el consenso alcanzado no fue alto.…”
Section: Discussionunclassified
“…Esta visión se aproxima más a la definición que propusieron los trabajadores de salud alemanes (12), y se aleja más de las visiones de las personas a las que les brindan atención. Este tipo de diferencias entre las conceptualizaciones del personal de salud y sus pacientes fue reportada, previamente, en estudios realizados con modelos explicativos de la diabetes en grupos poblacionales guatemaltecos, mexicanos, México-americanos y de Puerto Rico (25).…”
Section: Discussionunclassified